The Labor Market Story Behind Latin America's Transformation : LAC Semiannual Report, October 2012 - de la Torre, Augusto; Messina, Julian; Pienknagura, Samuel (Washington, DC, 2012)
After a robust recovery following the global crisis, Latin American and the Caribbean (LAC) has entered into a phase of lower growth dynamics: economic activity in the region is expected to expand by about 3 percent in 2012, after having grown at 4 percent in 2011 and 6 percent in 2010. This deceleration is not specific to LAC but is part of a global slowdown. World growth is indeed declining sharply, from 4.5 percent in 2011 to about 2.3 percent in 2012. Notably, the slowdown in middle-income regions has taken place in a highly synchronized manner: growth rates in LAC, Eastern Europe and South East Asia have fallen by a very similar magnitude (about 3 percentage points) between 2010 and 2012. While this synchronization reflects exogenous (global) forces the spillover to emerging markets of weaker activity in the world's growth poles, particularly Europe and China it also reflects endogenous (internal) dynamics, particularly the fact that many Middle Income Countries (MIC) had already reached in 2010-2011 the peak of their own business cycles. This synchronicity notwithstanding, the 2012 growth forecasts for individual countries in LAC are significantly heterogeneous, reflecting complex interactions between external and country-specific factors. The first chapter, which is shorter, concerns the economic juncture and growth prospects. The second chapter, which is longer and more substantive, deals with selected labor issues from both the structural and cyclical viewpoints.